Interventions and policies aimed at improving nutrition in Small Island Developing States: a rapid review - Catherine R. Brown; Kern Rocke; Madhuvanti M. Murphy; Ian R. Hambleton (Pan American Health Organization, 2022)
Objective. To describe features of nutritional interventions implemented in Small Island Developing States (SIDS) in the past 20 years. Methods. A rapid scoping review was conducted by searching PubMed and Web of Science databases for interventions conducted in SIDS that sought to improve the nutrition of their populations between 2000 and 2019 inclusive. The Noncommunicable diseases progress monitor 2020 was also examined to assess nutritional policies in SIDS. Results. A total of 174 interventions were implemented in 49 of the 58 SIDS. The greatest proportion were conducted in the Caribbean (75 interventions; 43%), with the Pacific region, and the Atlantic, Indian Ocean, Mediterranean and South China Sea region each implementing about 30% of interventions. Using the NOURISHING framework, most interventions (67%) were implemented at the community and national or policy level, using multiple components of the framework. The greatest proportion of interventions (35%) were educational and awareness raising. Restrictions on physical availability of and increased taxation on alcohol were the most commonly reported policies that were partially or fully achieved; restrictions on fats were the least commonly reported. These findings were generally consistent across the SIDS regions. Conclusions. There is a paucity of nutritional policies in SIDS; the reasons may be linked to their social, economic, and environmental vulnerabilities. Interventions should be expanded beyond education to encompass multiple components of the NOURISHING framework, with multisectoral inclusion to ensure stronger stakeholder collaboration and buy-in. A systematic review is warranted using a fuller range of sources to assess the effectiveness of interventions.